Cerebral vein thrombosis: from risk factors to recanalization and clinical outcomes. A review - Tatiana Yu. Batenkova (ZAO "Consilium Medicum", 2024)
Cerebral vein thrombosis or cerebral venous thrombosis (CVT) is a complex venous thromboembolic disease with a different clinical picture, etiology and multiple potential complications. The frequency of occurrence is 0.5-1% of all stroke cases. Clinical symptoms occur as a result of increased intracranial pressure caused by a violation of venous outflow and brain damage. CVT is associated with a wide range of clinical symptoms from isolated headaches (the most common symptom on admission, registered in 90% of cases) to focal deficits, seizures and changes in mental status. Careful collection of anamnesis with targeted identification of risk factors, full-fledged diagnosis and treatment contribute to achieving a favorable clinical outcome in patients. The article focuses on the degree of recanalization of cerebral venous thrombosis, assessment of venous collaterals according to the degree of Qureshi and clinical outcomes depending on risk factors. These indicators are little studied at present.